1998
DOI: 10.1177/104990919801500512
|View full text |Cite
|
Sign up to set email alerts
|

Hospice research: Challenges, opportunities and rewards

Abstract: Hospice and research have had a long-standing and, at times, strained relationship. Early studies, most notably the National Hospice Study, were instrumental in the passage and ongoing support of the hospice Medicare benefit and the growth and development of the hospice movement in the United States. Increasingly, hospices are involved in research as a result of managed care and other demands for outcome measures. Yet, it is often difficult to define and measure much of what hospice is about--quality of life, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…It is important that relationships in the community be established and nourished to enhance education and research about quality of care, and to improve the clinical practice of students, faculty, and staff. Kovacs 16 has addressed the need for collaboration between hospice personnel and university researchers in evaluating hospice care, noting that hospice and research have had a strained relationship over the years.…”
Section: Discussionmentioning
confidence: 99%
“…It is important that relationships in the community be established and nourished to enhance education and research about quality of care, and to improve the clinical practice of students, faculty, and staff. Kovacs 16 has addressed the need for collaboration between hospice personnel and university researchers in evaluating hospice care, noting that hospice and research have had a strained relationship over the years.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a secondary role of practitioner was continually present. Benoliel (1975) noted that research with dying persons creates a unique set of circumstances in which the research role becomes secondary to the nursing role (Dean & McClement, 2002;Kovacs, 1998). When potential or active participants were found in severe distress, the nurse as patient advocate was without question the primary role (Raudonis, 1992).…”
Section: Palliative and End-of-life Carementioning
confidence: 99%
“…Although the investigator's primary role was nurse researcher, the fundamental charge was to protect human subjects; hence, a secondary role of practitioner was always in mind. Investigations with dying people create a unique set of situations (Benoliel, 1975b), in which the research role becomes secondary to the nursing role (Dean & McClements, 2002;Kovacs, 1998). When potential participants were found in severe physical distress, the nurse as patient advocate became the primary role (Raudonis, 1994).…”
Section: Issues Of Assistancementioning
confidence: 99%
“…In their review of ethical issues in conducting research with palliative care populations, Kristjanson, Hanson, and Balneaves (1994) found that almost half of the projects included participants who were in advanced stages of illness. Dying people suffer diminished physical and, often, impaired cognitive and psychological states (Kovacs, 1998;Kristjanson, Hanson, & Balneaves, 1994); therefore, participant attrition is an expected occurrence (Dean & McClement, 2002;Dush & Cassileth, 1985, Kinzbrunner, 1995. As a result, researchers are often torn between securing an adequate study population and enrolling less than competent participants (Kristjanson et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation